CEFPIROME (CPR) IN THE TREATMENT OF PATIENTS WITH SURGICAL INFECTIONS - MORIMOTO KEN; KINOSHITA HIROAKI; NAKATANI SHUICHI; SAKAI KATSUJI; FUJIMOTO MIKIO; OHNO KOHICHI; UEDA TAKAMI; MORIMOTO YUZURU; OHMORI KUNIO; HIRATA SANAE; MURAMATSU HIDEYUKI; MIZUGAMI KENJI; et al. (CHEMOTHERAPY, 1991)
Between September 1988 and January 1990, we gave cefpirome (CPR) to five subjects after surgery and studied the pharmacokinetics of the drug. In the same period, we treated 20 patients with surgical infections with the same drug and evaluated its clinical effects.1. In the basic study, 1 g was given intravenously over a 30 min. period. The peak levels in the plasma, 78.4-114 μg/ml, were at around the end of this time. The peak levels in the bile, 10.7-148 μg/ml, were at hours 2-5, depending on the patient. At hours 5 and 6, the range was 10.4-114 μg/ml.2. In the 20 patients with surgical infection, the clinical efficacy of the drug was excellent in seven, good in nine, fair in one, and poor in two, with an efficacy rate of 84%.3. The bacteriological response was evaluated in the 16 patients, for whom the species of the probable causative organism could be identified. The bacteria were eradicated in ten patients, decreased in one, were replaced in one, and persisted in four, with an eradication rate of 69%.4. For the six strains of Pseudomonas aeruginosa isolated, the highest MIC was 6.25 μg/ml, so this drug should be effective toward this species. Two strains of Staphylococcus aureus were isolated, one of which was resistant to methicillin. It was not eradicated. 1988年9月から1990年1月までに大阪市立大学医学部第2外科およびその関連施設で取り扱った外科的感染症20例に対するcefpirome (CPR) の使用経験を検討するとともに総胆管結石術後のT-tubeドレナージ中, あるいはPTCD中の5例に対する本剤の胆汁移行を検索し, 以下の結果を得た。1) 本剤1gを30分間点滴静注された5例の血漿中濃度は点滴終了時で78.4～114μg/mlのピークレベルとなり, 6時間後では3.11～15.7μg/mlにまで低下したのに対し, 胆汁中濃度は点滴開始後2～5時間で10.7～148μg/mlのピークレベルに達し, 5～6時間の分画でも10.4～114μg/mlのレベルを維持していた。2) 本剤の臨床効果判定は評価可能19例のうち, 著効7例, 有効9例, やや有効1例.無効2例で, 有効率は84.2%であった。3) 細菌学的効果は16例で評価され, 消失10例, 減少1例, 菌交代1例, 不変4例であり, 消失率は68.8%, 分離菌別に細菌学的効果をみると, 分離菌株29株中消失21株, 不変8株で消失率72.4%であった。4) 今回検討された症例中, 治療開始時, 緑膿菌を認めた6例でのMICは最高値で6.25μg/ml程度で本剤の有効性が期待される。黄色ブドウ球菌は2例に検出され, 1例はmethicillin-resistant Staphylococcus aureus (MRSA) で除菌されなかった。